A new method for the evaluation of pelvic organ prolapse in women using a three-dimensional optic scanner. Issue 7 (July 2016) - Kasyan, George; Tupikina, Nataliya; Pushkar, Dmitry
Abstract Introduction and hypothesis Modern classifications of pelvic floor movements are based on pelvic floor assessment in a static midsagittal plane. This study presents a new and potentially useful 3D noninvasive tool for studying pelvic floor mobility in women with pelvic organ prolapse (POP). Materials and methods Thirty-four patients with POP [grade ≥3 using the Pelvic Organ Prolapse Quantification (POP-Q) system] and 30 healthy volunteers (controls) at rest and during Valsalva maneuver were scanned using an Artec™ 3D optic portable scanner and 3D pelvic floor models were generated. We calculated the volume of the prolapsed vaginal wall using dynamic prolapse increment (DPI), which is defined as an increase in prolapse volume from rest to its maximal Valsalva probe [DPI = (Vval – Vrest) / Vrest %)]. Results In the control group, the average DPI was 28 % (16–51 %). As the DPI in patients with POP varied widely, two subgroups were identified. In the first subgroup, the average DPI was 290 % (125–437 %), whereas it was only 48.8 % (41–55 %) in the second subgroup. Prolapse volume in subgroup 1 was not due to the most prominent component of POP but was induced by enlargement of the prolapsed vaginal wall from other components, such as a cystocele or enterocele, which was evident only during the 3D procedure and could not be validated by the POP-Q system. Conclusions In addition to existing methods, 3D modelling is a useful tool for evaluating pelvic floor mobility. Further investigation of the pelvic floor dynamic features in women is necessary.